Performance Analysis of Islamic Commercial Banks (Comparative Study of Indonesian Islamic Banks and Bank Muamalat Indonesia) Period 2021-2022 - Abdullah; Adi Fadli; Sanurdi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In Indonesia, the development of sharia banking has experienced significant progress.. So in such conditions, Sharia commercial banks must be in a healthy condition and full of loyalty in accordance with their name, namely Sharia-based. This research is limited to analyzing the performance of Bank Syariah Indonesia and Bank Muamalat Indonesia specifically, for the 2021-2022 period. This research is qualitative research with a descriptive approach that uses secondary data, annual financial reports for the 2021-2022 period at Bank Syariah Indonesia and Bank Muamalat Indonesia through statistical data analysis in the form of numbers (quantitative). Meanwhile, financial performance measurement uses the RGEC method based on Financial Services Authority Regulation (POJK) No. 10/SEOJK.03/2014. Sharia performance measurement uses the Islamicity Performance Index (IPI) method. The results of this research based on quarterly financial performance measurements for the 2021-2022 period show that the ratio performance at Bank Syariah Indonesia consists of NPF 2.87%, FDR 76.62%, ROA 1.84%, NOM 2.02% and CAR 22.30%, while Bank Muamalat Indonesia showed an NPF ratio of 2.97%, FDR 49.45%, ROA 0.06%, NOM 0.13%, and CAR 18.97%, so it can be concluded that the performance of both banks is in the good category, However, Bank Syariah Indonesia has better performance than Bak Muamalat and there is no significant difference between Bank Syariah Indonesia and Bank Muamalat Indonesia in the NPF ratio.